Root(ed) : a collection of poems - Atifa Othman (2019)
Root(ed) is a collection of 23 poems, accompanied by an exegesis exploring its themes and poetics. These poems are divided according to two sections— (s) and (ed), each based on suffixes to be added to the word “root.” Root(ed) was conceptualised because of a desire to go back to my roots, and make sense of how my ethnic and cultural experiences interact with other strands of my selfhood. The poems in this collection reflect upon being composed of disconnected angles, a term borrowed by American poet Adrienne Rich. Rich writes: “Sometimes I feel I have seen too long from too many disconnected angles: white, Jewish, anti-Semite, racist, anti-racist, [...] split at the root that I will never bring them whole” (481). She describes the fragmented selfhood one feels when made up of several identities that contradict each other. This collection is based on a similar feeling of being split at the root. The poems written are fuelled by the need to reconcile the disconnected angles in my identity. Root(ed) examines the extent to which I am rooted in each part of my identity. It addresses themes of race, family, queerness and nationhood, delving into how these different strands entangle into each other and require a constant unravelling. The poems in Root(ed) thus question whether a marginalised individual can feel fully immersed in their roots, responding to the anxiety of constantly feeling trapped in a cutthroat and fast-paced world that values capitalist productivity.